2014
DOI: 10.1111/ans.12906
|View full text |Cite
|
Sign up to set email alerts
|

Operative efficiency and accuracy of patient‐specific cutting guides in total knee replacement

Abstract: Patient-specific cutting guides make accurate resections. Operative and tourniquet times and the number of trays used were no different to standard TKRs. Further investigation is needed to determine whether patient-specific cutting guides improve post-operative alignment and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 7 publications
1
20
0
1
Order By: Relevance
“…Apart from orthopedics (guides for knee arthroplasties), 3D-printed surgical guides were also used in neurosurgery, dental surgery, spinal surgery, and maxillofacial surgery. 28 of the 53 studies that mentioned reduced operation room time also supported this claim with numbers or statistics [ 39 , 74 , 81 , 84 , 118 , 131 , 132 , 135 , 136 , 140 , 141 , 145 , 151 , 152 , 162 , 175 , 177 , 181 , 190 , 194 , 196 , 200 , 207 , 210 212 , 219 ]. Increased procedural time was seen in seven papers, of which five supported this with numbers or statistics [ 62 , 73 , 125 , 143 , 153 , 161 , 225 ].…”
Section: Resultsmentioning
confidence: 87%
“…Apart from orthopedics (guides for knee arthroplasties), 3D-printed surgical guides were also used in neurosurgery, dental surgery, spinal surgery, and maxillofacial surgery. 28 of the 53 studies that mentioned reduced operation room time also supported this claim with numbers or statistics [ 39 , 74 , 81 , 84 , 118 , 131 , 132 , 135 , 136 , 140 , 141 , 145 , 151 , 152 , 162 , 175 , 177 , 181 , 190 , 194 , 196 , 200 , 207 , 210 212 , 219 ]. Increased procedural time was seen in seven papers, of which five supported this with numbers or statistics [ 62 , 73 , 125 , 143 , 153 , 161 , 225 ].…”
Section: Resultsmentioning
confidence: 87%
“…Some researchers smartly came up with a way to study PSI accuracy without using X-ray measurement. In these studies, the amount of bony resection was measured and compared with planned osteotomy [18][19][20][21][22]. However, the results of these studies were covered with controversy.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature is not consistent with respect to the reduction in operative room time with PSI [ 3 , 5 , 6 , 24 26 ]. We believe that the reasons for this absence of published information include relatively limited surgical experience and problems in guide design.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PSI guides used during primary TKA improve operative room efficiency with fewer outliers [ 3 , 4 ]. In contrast, other data has shown only a marginal improvement in operative room efficiency in PSI compared to similar arthroplasties performed with CI [ 5 , 6 ]. This difference may be due to a lack of surgical experience and the relatively small number of patients studied to date.…”
Section: Introductionmentioning
confidence: 92%